Health service performance and human development against COVID-19 in Mexico. - Tlapa-Pale, Arturo; Mendoza-Longoria, Lilia Maricela; Picazzo-Palencia, Esteban; Rangel-Esquivel, José Manuel (Horizonte Sanitario, 2025)
Objective: To analyze the performance of healthcare services by constructing a Healthcare Services Performance Index (HSPI) and its relationship with indicators of COVID-19 pandemic management outcomes, as well as its relationship with the Human Development Index (HDI) in Mexico. Materials and methods: A cross-sectional and descriptive study was conducted, analyzing healthcare services in the 32 federal entities in the year 2021. The HSPI was calculated using the Equal Weights method. The score for each variable and the HSPI was classified using the scale based on the self-assessment instrument for compliance with the International Health Regulations. Mortality rate, lethality, prevalence, and incidence were calculated as indicators of COVID-19 pandemic outcomes. Pearson correlation analysis was applied to analyze the intensity and direction of each of the relationships. Results: The performance of healthcare services is unequal in all federal entities, with those in the southern zone having lower scores. At the national level, performance is still developing. The HSPI showed that there is better performance of healthcare services as there are higher mortality, prevalence, and incidence rates. The correlation of HSPI and HDI demonstrated that there is better performance of healthcare services as there is a higher HDI. Conclusions: The HSPI reflects better performance of healthcare services in regions with higher HDI, suggesting that well-being conditions influence the quality and accessibility of medical care. However, the pandemic has highlighted the structural weaknesses of the Mexican healthcare system, as well as the social and economic inequalities affecting its functioning and responsiveness.